EVALUASI PENGENDALIAN INTERNAL UNTUK MENCEGAH TERJADINYA FRAUD DAN ERROR ATAS PERSEDIAAN TOKO BUNGA HIDUP BLOSSOM DI SURABAYA - Stephanie Angelina Santoso; Adhicipta Raharja Wirawan (Perpustakaan Universitas Surabaya, 2018)
This study purposes to minimize the potential of fraud and error in a business entity. A business entity needs to apply internal controls to provide confidence that data is processed correctly, assets and information are safeguarded, and applicable laws are followed. This study was conducted by comparing the internal condition of the company with several theories, such as the theory of COSO Framework and Fraud Triangle theory, with the research object Toko Bunga Hidup Blossom Surabaya. Data was collected by interview method, observation, and document analysis. This study found many weaknesses of internal controls in Toko Bunga Hidup Blossom that could potentially lead to fraud and error. Where one of the causes is the owner’s lack of attention about internal control. Therefore, researchers give recommendations in the form of drafting regulations and written sanctions, improving store security systems, and evaluating employee performance.